PELATIHAN PEMBUATAN KOLAM TERPAL UNTUK BUDIDAYA IKAN SISTEM RESIRKULASI BIOFLOK DI DESA GONDANG, KECAMATAN GANGGA, KABUPATEN LOMBOK UTARA - Abidin, Zaenal; Setyono, Bagus Dwi Hari; Mandalika, Eka Nurminda Dewi (Jurnal Abdi Insani, 2025)
Fish farming technology is progressively advancing in the techniques utilized and the rearing media. A tarpaulin tank is reasonably simple and inexpensive. Therefore, it is suitable for those seeking to cultivate fish with constrained land and financial resources. This project aims to train the stakeholders - in this case, members of the "Mula Mele Bersih" farmer group - to construct tarpaulin ponds that can be used to cultivate tilapia using the recirculation-biofloc system. This training involved 12 farmer group members in Gondang Village, Gangga District, North Lombok Regency. This community service activity began with socialization, counseling, materials and equipment provision, tarpaulin pond assembly, water installations, aeration installations, and pond trials. The materials used were tarpaulin, 6 mm wire mesh, aeration hoses, water hoses, air diffusers, tarpaulin, various sizes of pipe, and water taps. The equipment needed was a hot gun, cutting tools, and a drill. The training was carried out accompanied by a demonstration. This activity produced 5 tarpaulin ponds that were ready for tilapia cultivation using the recirculation-biofloc system. The activity began with making the pond base, assembling the frame, installing the tarpaulin and tarpaulin protectors, installing aeration, and making a sedimentation place. The fact that partners successfully created ponds indicates that the pond is simple, easy to construct, and easy for other communities to replicate.